Metaplastic breast carcinomas: a report of six cases - Shahrun NS,; Rohaizak M,; Naqiyah I,; Nurismah MI, (Penerbit UKM, 2009)
Metaplastic breast carcinomas (MBCs) are rare primary breast malignancies characterized histologically by carcinoma of two epithelial types or co-existence of carcinoma with non-epithelial cellular elements. They are aggressive tumours that carry poor prognosis. We reviewed the pathologic features and clinical outcomes of MBCs seen in our institution between the years 2000 to 2007. Out of 471 breast cancer patients, six female patients were histologically-proven to have MBCs giving an incidence rate of 1.3%. The patients comprised four Malays and two Indians and their mean age was 51 years old. Five patients underwent mastectomy (four with axillary clearance and one without) and one had wide local excision with axillary clearance. Axillary lymph node involvement was seen in four patients (three with epithelial only type tumour and one with the biphasic tumour). In all the cases, the tumours were bigger than 5 cm in diameter (T3), grade 3 and estrogen receptor negative. Five patients received chemotherapy while one refused. All of the patients had tumour recurrence with a mean time of recurrence of 9 months. In conclusion, metaplastic breast carcinomas are rare and aggressive tumours usually affect the post menopausal age group. They present as aggressive, large sized, high grade tumours that are estrogen receptor negative. Tumour size and axillary lymph node involvement indicate poor prognosis. Despite treatment with chemotherapy and radiotherapy, these patients have high risk of local recurrence and distant metastases which are potentially fatal.